2010
DOI: 10.1063/1.3392768
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of water droplet binary collisions and description of outcomes with a symmetric Weber number

Abstract: The outcomes of binary collisions of water droplets are investigated experimentally for the range of parameters of a spray system used during a severe nuclear reactor accident. Droplets diameters range from 220 to 450 m with a diameter ratio between 0.5 and 1 and impact velocities between 3 and 10 m s −1 . Values of the Weber number based on the small droplet size are between 20 and 280. For droplets with a Weber number up to 120, results in a map of impact parameters versus Weber number show the various regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 12 publications
2
58
0
5
Order By: Relevance
“…Previous studies [25][26][27] have demonstrated that droplet separation is suppressed and hence droplet coalescence is promoted by increasing the size ratio. It is known that droplet separation occurs, at relatively high Weber numbers, when the surface tension of the temporarily coalesced droplet cannot hold the excess kinetic energy of the collision.…”
Section: Collision Dynamics and Internal Mixing Of Dropletsmentioning
confidence: 99%
“…Previous studies [25][26][27] have demonstrated that droplet separation is suppressed and hence droplet coalescence is promoted by increasing the size ratio. It is known that droplet separation occurs, at relatively high Weber numbers, when the surface tension of the temporarily coalesced droplet cannot hold the excess kinetic energy of the collision.…”
Section: Collision Dynamics and Internal Mixing Of Dropletsmentioning
confidence: 99%
“…Interestingly, all VOF simulations for water droplets (Saroka et al 2012) of different size are clustered above the correlation, which indicates that some phenomena are not captured properly by these simulations. One result of Rabe et al (2010) for different sized water droplets is also found in this region. This point is just included for illustrating the fact that decreasing size ratio yields a shift of the triple point as well as Wec to the right (see Tang et al 2012).…”
Section: Characteristic Points In the Collision Mapsmentioning
confidence: 57%
“…with vd , a viscous dissipation coefficient, found experimentally to be equal to 0.92 and with dimensionless number ref/stre that is found to be 0.28 according to experimental results (Rabe, 2010). These three models describing the transition curves between collision regimes are described more in detail in Rabe (2010).…”
Section: Modelling Of Droplet Polydispersionmentioning
confidence: 99%
“…Rabe et al [27] proposed simple formulae expressing the boundaries of collision outcomes fields as a function of the symmetric Weber number. The final equation for the critical impact parameter ( represents the impact parameter for which the transition between two regimes is observed) at which the transition between reflexive separation and coalescence occurs is then Based on another balance of energies, the critical impact parameter for the transition between coalescence and stretching separation can be expressed as stre-coal = √We 2 stre + 8We stre We − We stre 4We…”
Section: Modelling Of Droplet Polydispersionmentioning
confidence: 99%
See 1 more Smart Citation